Bimbingan Klasikal Metode Project Base Learning Menggunakan Canva Untuk Meningkatkan Kemantapan Pengambilan Keputusan Karir Siswa - Pramesthiningrum, Galuh; Yakub, Elni; Donal, Donal (Universitas Palangka Raya, 2025)
Proper career guidance can help students understand themselves. High school students are in their late teens and are in a transitional phase, so they need to make the right decisions for their future careers. The purpose of this study was to determine the effect of Classical Guidance Project Based Learning Method using Canva to improve the Stability of Students' Career Decision Making. This study is quantitative with an experimental research type. The research design is one group pretest-posttest design. The data collection technique used a questionnaire with a Likert Scale. The data analysis used is descriptive analysis, T-test, and Product Moment Correlation Test. The results showed that the level of stability of students' career decision making before being given treatment was in the low category of 12.50% and dominant in the medium category of 87.5%. However, after being given treatment, it was in the high category of 22.50% and dominant in the very high category of 77.50%. There was a significant difference in the stability of students' career decision making between before and after treatment, namely an increase in aspects and the highest increase in aspects was exploration, which was 398 points. Then the classical guidance service using the project-based learning method using Canva had a positive influence of 54% in increasing the stability of career decision-making in grade XI students.